Contribution Independent Curriculum on Improving Morals and Understanding of Islamic Religious Education for Madrasah Aliyah Students - Wahyuni, Sri; Giantara, Febri; Nasution, Baktiar; Rahman, Abdul; Rafiqah, Lailan (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
This study discusses the Implementation of the Independent Curriculum to Improve Moral Understanding in Islamic Religious Education at Madrasah Aliyah Diniyah Puteri Pekanbaru. Frequent changes in the curriculum usually occur due to the change of the Minister of Education which has an impact on the unclear quality of education. The problems of the world of education that occur in Indonesia do not only occur in the quality of students due to frequent curriculum changes. So as to see the effectiveness of the implications of this Independent curriculum in forming students who are of high value with good morals. As the goal of education is to create faithful and pious humans who have good morals and ethics. This study aims to see the process of the Independent Curriculum at MA Diniyah Puteri Pekanbaru in implementing the Independent Curriculum to improve the quality of Indonesian Education. The research method used is a mixed method with Sequential Exploratory Design, a mixed approach with qualitative and quantitative research, with an Exploratory design. Data were collected from 58 out of 60 grade X and XI students who used the Independent Curriculum at MA Diniyah Puteri Pekanbaru. This study successfully formulated that the Independent Curriculum, morals and Islamic religious education are running as they should. In addition, it is supported by the results of interviews with Akidah Akhlak teachers. The results were evaluated with an authentic approach. This finding shows that the implementation of the Independent Curriculum is 55.9% of the influence of the Independent Curriculum on moral understanding of students. Supported by a superior program, namely a program for habituating polite attitudes that are instilled in students through spiritual activities, such as Tahsin, Tahfiz, and Sunnah Worship and reading al-Quran for two hours at the beginning of the learning process. [Penelitian ini membahas mengenai Implementasi Kurikulum Merdeka untuk Meningkatkan Pemahaman Moral Dalam Pendidikan Agama Islam di Madrasah Aliyah Diniyah Puteri Pekanbaru. Seringnya terjadi perubahan kurikulum biasanya terjadi karena pergantian Menteri Pendidikan yang berdampak pada mutu Pendidikan yang tidak jelas. Permasalahan dunia pendidikan yang terjadi di Indonesia bukan hanya terjadi pada kualitas peserta didik akibat perubahan kurikulum yang sering terjadi. Sehingga untuk melihat keefektivan dalam implikasi kurikulum Merdeka ini dalam membentuk peserta didik yang bernilai tinggi dengan moral yang baik. Sebagaimana tujuan Pendidikan adalah menjadikan manusia yang beriman dan bertakwa yang memiliki moral dan akhlak yang baik. Penelitian ini bertujuan untuk melihat proses Kurikulum Merdeka di MA Diniyah Puteri Pekanbaru dalam mengimplementasikan Kurikulum Merdeka untuk meningkatkan kualitas Pendidikan Indonesia. Metode penelitian yang digunakan metode campuran dengan Sequential Exploratory Design, pendekatan campuran dengan penelitian kualitatif dan kuantitatif, dengan desain Eksploratory. Data dikumpulkan 58 dari 60 siswa kelas X dan XI yang menggunakan Kurikulum Merdeka di MA Diniyah Puteri Pekanbaru. Penelitian ini berhasil merumuskan bahwa Kurikulum Merdeka, moral dan Pendidikan agama islam berjalan sebagaimana mestinya. Selain itu didukung oleh hasil wawancara terhadap guru Akidah Akhlak. Hasilnya dievaluasi dengan pendekatan otentik. Temuan ini menunjukkan bahwa implementasi Kurikulum Merdeka sebesar 55,9% adanya pengaruh Kurikulum Merdeka dalam pemahaman moral terhadap peserta didik. Didukung dengan program unggulan yaitu program pembiasaan sikap sopan santun yang ditanamkan kepada siswa melalui kegiatan kerohanian, seperti Tahsin, Tahfiz dan Ibadah Sunnah serta membaca al-Quran dua jam di awal proses memulai pembelajaran].